2020
DOI: 10.3928/1081597x-20200828-02
|View full text |Cite
|
Sign up to set email alerts
|

Multizonal Design Multifocal Intraocular Lens–Induced Astigmatism According to Orientation

Abstract: PURPOSE: To evaluate the differences in intraocular lens (IOL)–induced astigmatism according to differences in orientation of a multizonal multifocal IOL, the Precizon Presbyopic NVA IOL (Ophtec BV). METHODS: The clinical study reviewed 80 eyes from 40 patients with cataracts who underwent Precizon Presbyopic IOL implantation. Residual astigmatism, as measured by autorefraction and manifest refraction, was investigated using vector analysis of eyes impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 30 publications
2
14
1
Order By: Relevance
“…Although zero-defocus VA was better than predicted from our optical measurements in those clinical studies, at − 1 D, the MTF-based prediction appears to overestimate VA. In our study, a VA value of 0.05 logMAR was predicted, but for Eom et al, it was 0.1 logMAR [ 28 ]. We noted a similar difference in the prediction for PanOptix, which, besides clinical factors, may also indicate the need for refinement of the applied VA-prediction formula.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Although zero-defocus VA was better than predicted from our optical measurements in those clinical studies, at − 1 D, the MTF-based prediction appears to overestimate VA. In our study, a VA value of 0.05 logMAR was predicted, but for Eom et al, it was 0.1 logMAR [ 28 ]. We noted a similar difference in the prediction for PanOptix, which, besides clinical factors, may also indicate the need for refinement of the applied VA-prediction formula.…”
Section: Discussioncontrasting
confidence: 56%
“…Eom et al enrolled 40 patients implanted with the Precizon and assessed IOL-induced astigmatism [ 28 ]. That study found an increase in astigmatism related to the IOL ranging from 0.68 ± 0.58 D to 1.05 ± 0.81 D, depending on the lens orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After that the lenses center and the camera were precisely aligned so that the image focus was on the camera’s sensor. The 1951 USAF resolution chart was illuminated by 555 nm LED light, and the image formed by the model eye was obtained by the CMOS camera [ 14 , 15 ]. The trial lens was placed in front of the model eye to obtain defocus image between − 2.50 D and + 1.00 D in 0.50 D intervals [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The images were converted to through-focus modulation transfer function (MTF) in the horizontal and vertical directions using the MatLab (Mathworks, Inc., Natick, MA) [ 17 ]. The root mean square of the horizontal and vertical MTF (MTF RMS ) was calculated using the following formula [ 15 ]: …”
Section: Methodsmentioning
confidence: 99%